2022
DOI: 10.1111/petr.14375
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial prophylaxis and the rate of blood stream infections and Clostridioides difficile in pediatric stem cell transplantation: A single‐center retrospective study

Abstract: Background:The use of prophylactic antibiotics in the pre-engraftment period to minimize the risk of bacteremia is debatable given concerns of Clostridioides difficile (C. diff), antibiotics resistance, and disruption of gut microbiota. Methods:We retrospectively reviewed the rate and characteristics of bacteremia and C. diff infections within the first 100 days post-HSCT in all pediatric patients who received routine antibacterial prophylaxis during HSCT from 2015 to 2018. C. diff infection was defined by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…11,[29][30][31][32] Children undergoing HCT are particularly vulnerable due to unique and non-modifiable risk factors, 33 but data on the incidence in this specific population are unfortunately quite scarce 34 and with some controversy. 12,33,[35][36][37][38] One study reported an 8% incidence, with higher rates in patients transplanted specifically for acute leukemia. 36 In another study, the incidence was 10% in the first 100 days post-HCT in pediatric patients receiving antibacterial prophylaxis, without significant correlation with primary disease, prior CDI or GvHD.…”
Section: Childrenmentioning
confidence: 99%
See 3 more Smart Citations
“…11,[29][30][31][32] Children undergoing HCT are particularly vulnerable due to unique and non-modifiable risk factors, 33 but data on the incidence in this specific population are unfortunately quite scarce 34 and with some controversy. 12,33,[35][36][37][38] One study reported an 8% incidence, with higher rates in patients transplanted specifically for acute leukemia. 36 In another study, the incidence was 10% in the first 100 days post-HCT in pediatric patients receiving antibacterial prophylaxis, without significant correlation with primary disease, prior CDI or GvHD.…”
Section: Childrenmentioning
confidence: 99%
“…36 In another study, the incidence was 10% in the first 100 days post-HCT in pediatric patients receiving antibacterial prophylaxis, without significant correlation with primary disease, prior CDI or GvHD. 37 Recently, Ramanathan et al 38 performed a study on 826 patients with CDI after allogeneic-HCT between the start of conditioning and day 100 and a control group of 6723 patients without CDI. In this study, the incidence of CDI was higher in pediatric patients (2-18 years) at 18.7% than in adult patients at 10.2%.…”
Section: Childrenmentioning
confidence: 99%
See 2 more Smart Citations